Makna Padungku pada Komunitas Pamona di Kecamatan Pamona Pasulemba - Muh. Ali Jennah; Kaharuddin Nawing; Roy Kulyawan (Jurnal Kreatif Online, 2021)
This study aimed to describe the meaning of the Padungku tradition as the cultural identity of the community and to describe the meaning of padungku in the socio-religious context. This study used a qualitative research tradition. The unit of analysis in this study was the community in Pamona Pasulemba District, and the informants consisted of nine people, two of whom were bureaucrats, two traditional leaders, five of whom were community members who worked as farmers. Sampling was done by using the snoble sampling technique. Meanwhile, data and information were collected through interviews and documentation. The results showed that: 1) Padungku as the language of cultural identity has developed the meaning of the Peasants' Great Harvest Festival, into an annual celebration that is attended by various segments of society. Padungku also has a meaning as a means of social integration and social acculturation; 2) the animist belief system through the padungku tradition experiences transportation to the belief system according to religious teachings. Religion assesses its contribution to changing people's way of thinking and beliefs, but on the other hand, the padungku tradition also contributes to the activities of religious institutional infrastructure.